THE IMPLEMENTATION OF THE BRUNEI DARUSSALAM ASNAF ZAKAT EMPOWERMENT (PROPAZ) PROGRAMME: ANALYSIS OF THE 2017-2022 STUDY: IMPLEMENTATION OF THE BRUNEI DARUSSALAM ASNAF ZAKAT EMPOWERMENT (PROPAZ) PROGRAMME: ANALYSIS OF THE 2017-2022 STUDY - Muhammad Hassanali Bin Mahdzidi; Azme Matali (Maliyah : Jurnal Hukum Bisnis Islam, 2026)
Abstract Productive Zakat, through the Asnaf Zakat Empowerment Programme (PROPAZ) in Brunei Darussalam, is an initiative to empower the economy of the asnaf (zakat recipients) by providing capital, skills training and entrepreneurial guidance. This program aims to reduce the dependence of asnaf on traditional zakat assistance which is consumptive in line with Maqasid Syariah which emphasizes preservation (hifz al-mal) and well-being (hifz al-nafs). Persistent poverty among asnaf who receive zakat assistance, lack of facing various challenges including long-term monitoring, as well as challenges in the implementation of PROPAZ such as lack of business management skills and adequate entrepreneurship education. The objective of this study is to evaluate the implementation of PROPAZ and its alignment according to the principles of Maqasid Syariah in empowering the asnaf economy from 2017 to 2022. To analyse the implementation and effectiveness of the programme and to study the long-term impact of PROPAZ on the economic survival of asnaf. The study methodology uses qualitative research methods through the analysis of official documents (MUIB JUZWAB annual report) and studies in academic form. Data were analyzed thematically to assess the effectiveness of the program, its challenges and its suitability with Maqasid Shariah. The results of the study provide guidance to improve the PROPAZ monitoring system, strengthen entrepreneurship training and expand cooperation with the private sector. This study also contributes to the academic literature on productive zakat and serves as a reference for policymakers in formulating economic empowerment programmes that are in line with Islamic values. Keywords: Productive Zakat, Maqasid Shariah, Asnaf Zakat Empowerment Program (PROPAZ)zaka